(untitled) (Journal of Engineering, 2021)
The flow in a manifolds considered as an advanced problem in hydraulic engineering applications. The objectives of this study are to determine; the uniformity qn/q1 (ratio of the discharge at last outlet, qn to the discharge at first outlet, q1) and total head losses of the flow along straight and rectangular loop manifolds with different flow conditions. The straight pipes were with 18 m and 19 m long and with of 25.4 mm (1.0 in) in diameter each. While, the rectangular close loop configuration was with length of 19 m and with diameter of 25.4 mm (1.0 in) also. Constant head in the supply tank was used and the head is 2.10 m. It is found that outlets spacing and manifold configuration are the main factors affecting the uniformity of flow distribution and friction head losses along manifolds. For large value of outlets spacing, the uniformity coefficient (qn/q1) was found with greatest value of 0.96. Thus, the flow distribution improves with bigger spacing between outlets along manifold. For same manifold length, diameter, inlet head and spacing between outlets (S/L=0.079), the uniformity coefficient was found 0.881 or 88.1% for straight manifold and 0.926 for rectangular loop manifold. From the experimental data, a better uniformity is obtained from the rectangular loop manifold, this is because the friction head loss in rectangular loop manifold was lower than that in straight manifold. The lowest of total head losses was found with greatest outlet spacing along manifold, while the highest of total head losses was found with smallest outlets spacing along manifold. And, the lowest of total head loss was found with the rectangular manifold, while the highest of total head loss was found with the straight manifold.